Critical role of peripheral drug actions in experience‐dependent changes in nucleus accumbens glutamate release induced by intravenous cocaine. (28th October 2013) - Wakabayashi, Ken T.; Kiyatkin, Eugene A.
Abstract Recent studies reveal that cocaine experience results in persistent neuroadaptive changes within glutamate (Glu) synapses in brain areas associated with drug reward. However, it remains unclear whether cocaine affects Glu release in drug‐naive animals and how it is altered by drug experience. Using high‐speed amperometry with enzyme‐based and enzyme‐free biosensors in freely moving rats, we show that an initial intravenous cocaine injection at a low self‐administering dose (1 mg/kg) induces rapid, small and transient Glu release in the nucleus accumbens shell (NAc), which with subsequent injections rapidly becomes a much stronger, two‐component increase. Using cocaine‐methiodide, cocaine's analog that does not cross the blood–brain barrier, we confirm that the initial cocaine‐induced Glu release in the NAc has a peripheral neural origin. Unlike cocaine, Glu responses induced by cocaine‐methiodide rapidly habituate following repeated exposure. However, after cocaine experience this drug induces cocaine‐like Glu responses. Hence, the interoceptive actions of cocaine, which essentially precede its direct actions in the brain, play a critical role in experience‐dependent alterations in Glu release, cocaine‐induced neural sensitization and may contribute to cocaine addiction. <boxed-text content-type="graphic" id="jnc12472-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Using high‐speed amperometry with enzyme‐based biosensors in freely moving rats, we show that initial intravenous cocaine induces rapid, transient glutamate (Glu) release in the Nac (Nucleus accumbens), rapidly becoming a stronger, two‐component increase with subsequent injections. We show that the peripheral actions of cocaine, which precedes its direct central actions, play a critical role in experience‐dependent alterations in Glu release, possibly contributing to cocaine addiction.